Sucinolivolia torpida—a new genus and species of flea-beetles (Coleoptera: Chrysomelidae: Galerucinae) from Baltic amber - Bukejs, Andris; Biondi, Maurizio; Alekseev, Vitalii I. (Zootaxa, 2015)
Sucinolivolia torpida gen. nov. et sp. nov. (Coleoptera: Chrysomelidae: Galerucinae: Alticini) is described and illustrated from Eocene Baltic amber. The new monotypic genus is compared with fossil and extant flea-beetle genera. Sucinolivolia gen. nov. is similar to the extant Livolia Jacoby and Orthaltica Crotch, but difference include the absence of an antebasal pronotal sulcus, not crenulate lateral pronotal margins, possessing very short genae, more robust legs, and the shape of tibiae. Including this new record, six described species of Alticini are known from Baltic amber.